Penerapan Nilai-Nilai Etika Dalam Filsafat Pendidikan Untuk Membangun Karakter Siswa - Ribka Br Keliat; Usman Alhudawi (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
The purpose of this study is to find out the application of ethical values of educational philosophy in building students' character. This research method uses a qualitative method with data collection techniques through interviews and field observations. The data analysis technique uses qualitative analysis. The results of the study show that the inclusion of the character education program in the curriculum of SMP Setia Budi Binjai is considered a significant and valuable investment based on the findings of the study. The program's success in shaping and improving children's morals and ethics highlights the importance of building and promoting a systematic and sustainable character education program in schools. This study highlights the value of character education as a component that helps children's overall development, not just as a complement to the curriculum. As a result, when developing and implementing curricula in schools, educators and policymakers need to pay serious attention to character education.